P-580 Cumulative live birth rate of oocyte in-vitro maturation with a pre-maturation step in women with polycystic ovary syndrome or high antral follicle count. (30th June 2022) - Pham, H; Le, A; Nguyen, A; Ha, U; Nguyen, T; Pham, T; Ho, T; Vuong, L
Abstract: Study question: What is the cumulative live birth rate (CLBR) at 24 months of women undergoing oocyte in vitro maturation (IVM) a with pre-maturation step (CAPA-IVM)? Summary answer: The CLBR at 24 months with CAPA-IVM was 38.2%. What is known already: IVM with a pre-maturation step, known as capacitation IVM (CAPA-IVM) improves the competence of oocytes matured in-vitro by sustaining meiotic arrest to allow the synchronization of cytoplasmic and genetic maturation of the oocytes. Results from a randomized controlled trial showed that CAPA-IVM resulted in a live birth rate after the first transfer of 35.2% which was non-inferior to IVF. There is a lack of data on cumulative live birth following CAPA-IVM. Study design, size, duration: A multi-center, retrospective study, performed at IVFMD, My Duc Hospital and IVFMD Phu Nhuan, My Duc Phu Nhuan Hospital from 1 January 2017 to 31 December 2019. Participants/materials, setting, methods: All women with polycystic ovary syndrome (PCOS) or high antral follicle count (AFC) treated with a CAPA-IVM cycle were recruited to the study. All embryos were frozen at day 3. Cumulative live birth was difined as at least one live birth resulting from initiated CAPA-IVM cycle. If the women did not return for embryo transfer, outcomes were followed up until 24 months from aspiration day. Logistic regression was performed to assess which factors predicted CLBR. Main results and the role of chance: Between 1 January 2019 and 31 December 2019, there were 374 eligible women included in the study, among them, 368 patients had embryos for transfer (98.4%) and six patients had no embryo for transfer (1.6%). A total of 496 frozen embryo transfer (FET) cycles from 368 patients were performed. Mean age and body max index (BMI) were 29.5±3.21 years and 22.3±3.09, respectively. The maturation rate was 63.2%. The median number of embryos was 4.0 [2.00; 6.00]. The cumulative clinical pregnancy rate was 60.4%, cumulative ongoing pregnancy rate was 51.6%. At 24 months after starting the treatment, the CLBR of CAPA-IVM was 38.2%. Multivariate analysis showed that patient age and number of metaphase II oocytes were the predictive factors for cumulative live birth after CAPA-IVM. Limitations, reasons for caution: The study limitation derives from its retrospective nature. The generalizability of the study may be limited due to the single ethnicity group. Wider implications of the findings: In patients with PCOS or high AFC, CAPA-IVM was viable and resulted in acceptable CLBR. CAPA-IVM may be the first-line treatment for women with PCOS or high AFC requiring assisted reproduction. Trial registration number: not applicable